Ambiental factors and sex effects on calving interval of Nelore females - Viana, Hildo Áurio; Ferreira, Paulo Roberto C. (Pesquisa Agropecuaria Brasileira, 2014)
Studying the calving interval of Nelore females, the following variables were determined: calf sex, year and month of previous calving, and calving parity. Based on the multiple regression analysis by the stepwise method, only the three last variables did significantly affect the dependent variable calving interval. From a total of 1,255 observations the average interval was 13,65 ± 3,7 months with CV = 24%. The year of previous calving determined a negative linear curve for intervals, while the month of previous calving and calving parity affected the intervals in a negative guadratic way. Food and reproductive management seemed to explain the result obtained during the five years studied.